Impact of different CAD software programs on marginal and internal fit of provisional crowns: An in vitro study - Kizilkaya, Ayse Rencber; Kara, Aybuke (Cell Press, 2024)
Statement of the problem: Different CAD software programs used for designing crowns show variations in marginal and internal fit. Marginal and internal discrepancies may cause poorly fitting crowns. Purpose: The aim of this study was to compare the marginal and internal fit of single crown temporary restorations designed using three different CAD software programs. Materials and methods: Dentbird, Exocad and Inlab 20 were used to design temporary single crowns using the same cement gap. Three experimental groups (n = 10/group) were formed based on the CAD software used. Geomagic Control X three-dimensional analysis software was used to compare the marginal and internal fit among the groups. Measurements were obtained at nine different thickness points. IBM SPSS Statistics, version 22 was used for all statistical analyses. Results: Among the CAD software programs tested, Dentbird produced the best internal fit on the buccal surface and the best marginal fit on both buccal and mesial surfaces. Exocad achieved the best values on the distal surface for both internal and marginal fit, while Inlab showed the best values on the mesial surface for internal fit and on the palatal surface for marginal fit. Conclusions: The Dentbird CAD software program provided the most accurate fit values that closely matched the design. The marginal and internal fit oftemporary crowns may vary depending on the CAD software used.
Keywords: Dentbird; Exocad; Geomagic; Inlab; Internal clearance; Marginal fit; Software